Melatonin increases the expression of insulin-like growth factor I in rats with carbontetrachlorid-induced hepatic damage - Oner, Jale; Kus, Ilter; Oner, Hakan (My University, 2009)
The purpose of this study was to investigate, whether or not melatonin has a role in the prevention of CCl4,-induced hepatotoxicity in rat by means of IGF expression. The animals used in study were grouped as following: Control, CC14 injected group and CC4 + melatonin injected group. Tissue samples were examined using immunohistochemistry and obtained data were evaluated statistically. IGF-I expression observed in hepatocytes was weakest in CCL injection group. Melatonin administration increased IGF-I expression in hepatocytes. The HSCORE value of the CC14 injected group was lower than that of other groups. The highest HSCORE value belonged to CC14 + melatonin injected group. On the basis of the data in the present study, we suggest that melatonin secreted by the pineal gland may have preventative role in hepatic damage by increasing IGF-I releasing. © Medwell Journals, 2009.
Keywords: Carbon tetrachloride; Hepatotoxicity; IGF-I; Immunohistochemistry; Melatonin; Rat